2018
DOI: 10.1021/acsmacrolett.8b00116
|View full text |Cite|
|
Sign up to set email alerts
|

Consequences of Grafting Density on the Linear Viscoelastic Behavior of Graft Polymers

Abstract: The linear viscoelastic behavior of poly­(norbornene)-graft-poly­(±-lactide) was investigated as a function of grafting density and overall molar mass. Eight sets of polymers with grafting densities ranging from 0 to 100% were synthesized by living ring-opening metathesis copolymerization. Within each set, the graft chain molar mass and spacing between grafts were fixed, while the total backbone length was varied. Dynamic master curves reveal that these polymers display Rouse and reptation dynamics with a shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
140
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(148 citation statements)
references
References 58 publications
3
140
0
Order By: Relevance
“…Several studies investigated the zero shear viscosity η 0 as a function of total molecular weight for different series of loose and dense bottlebrushes with either short chain branches (SCB) [13,18,19,24,[29][30][31]57] or long chain branches (LCB). [11,30] Within these bottlebrush series, two characteristics out of n sc , n g , and n bb are fixed and one of them is varied in the series.…”
Section: Zero Shear Viscositymentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies investigated the zero shear viscosity η 0 as a function of total molecular weight for different series of loose and dense bottlebrushes with either short chain branches (SCB) [13,18,19,24,[29][30][31]57] or long chain branches (LCB). [11,30] Within these bottlebrush series, two characteristics out of n sc , n g , and n bb are fixed and one of them is varied in the series.…”
Section: Zero Shear Viscositymentioning
confidence: 99%
“…Figure 5a presents the reduced η 0 for five bottlebrush series and a linear series at a reference temperature T ref = T g + 34 °C. [31] It was shown that η 0 versus M w has two different scaling regimes 1 and 3, which could be related to Rouse and reptation dynamics, respectively. These bottlebrushes were synthesized via ROMP of ω-norbornenyl polylactide macromonomers.…”
Section: Zero Shear Viscositymentioning
confidence: 99%
See 2 more Smart Citations
“…The linear viscoelastic behavior of poly(norbornene)‐gr‐PLA obtained by living ROMP was studied, depending on the grafting density and total molar weight (Figure ) . It turned out that resulting polymers demonstrate Rouse and reptation dynamics with a sharp transition in zero‐shear viscosity data, demonstrating that grafting density strongly affects the entanglement molar weight.…”
Section: (Co) Polymerizationmentioning
confidence: 99%